2000
DOI: 10.1002/1097-4628(20010118)79:3<517::aid-app150>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

New chlorine-resistant polyamide reverse osmosis membrane with hollow fiber configuration

Abstract: New asymmetric hollow fiber reverse osmosis (RO) membrane was developed from a new chlorine‐resistant copolyamide [4T‐PIP(30)] with a piperazine moiety by a conventional phase‐separation method. The new 4T‐PIP(30) hollow fiber membrane has the same low‐pressure RO performance as cellulose triacetate hollow fiber membrane (FR = 205 L/m2 day, Rj = 99.6%) and superior chlorine resistance as well as pH resistance to conventional aramid RO membranes. Structural analysis and viscoelastic study revealed that the new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Le Roux et al (2015) reported DBP occurrences in two RO desalination plants as well as one MSF plant. One RO plant was equipped with polyamide (PA) membranes that can offer high permeate flux and adequate salt rejection (Fujioka et al, 2012) and the other with cellulose triacetate (CTA) membranes that are chlorine-resistant (Konagaya et al, 2001). Very low level of THMs (0.36 mg/L) were detected in the 1st pass permeate of the former RO plant with no detectable level of HAA and HANs, while THM levels in the latter RO plant increased from the chlorinated intake (14.5e18.4 mg/L) to the 1st pass permeate (39e67 mg/L).…”
Section: Dbp Occurrences In Distillate and Ro Permeatementioning
confidence: 99%
“…Le Roux et al (2015) reported DBP occurrences in two RO desalination plants as well as one MSF plant. One RO plant was equipped with polyamide (PA) membranes that can offer high permeate flux and adequate salt rejection (Fujioka et al, 2012) and the other with cellulose triacetate (CTA) membranes that are chlorine-resistant (Konagaya et al, 2001). Very low level of THMs (0.36 mg/L) were detected in the 1st pass permeate of the former RO plant with no detectable level of HAA and HANs, while THM levels in the latter RO plant increased from the chlorinated intake (14.5e18.4 mg/L) to the 1st pass permeate (39e67 mg/L).…”
Section: Dbp Occurrences In Distillate and Ro Permeatementioning
confidence: 99%
“…In comparison to CTA RO membranes, PA membranes usually have high permeability and can be operated in a much wider pH range [12]. Nevertheless, CTA RO membranes are chlorine-resistant and thus residual chlorine can be maintained at up to 1 mg/L in the RO feed [13]. In fact, the CTA RO filtration in combination with chlorination can suppress biological growth on RO membrane surfaces and prevent an increase in feed pressure caused by membrane fouling in seawater desalination applications [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%